2001
DOI: 10.1542/peds.107.1.e11
|View full text |Cite
|
Sign up to set email alerts
|

Peptostreptococcus asaccharolyticus Renal Abscess: A Rare Cause of Fever of Unknown Origin

Abstract: ABSTRACT. Renal abscess is uncommon in pediatrics and is rarely a cause of fever of unknown origin. We recently cared for a patient who presented with a 3-week history of fever. An indium scan ultimately led to the diagnosis of a renal abscess. Aspiration yielded Peptostreptococcus asaccharolyticus. This unusual case prompted a review of the clinical and microbiologic features of renal abscess in pediatric patients at our hospital over the past 10 years. Seven additional patients with a discharge diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…According to previous studies, renal abscess may result from hematogenous spread or ascending infections due to reflux or stasis of infected urine, and the most common pathogens isolated in children are E. coli and S. aureus [3, 4, 16]. In adults, the most frequent microorganisms yielded on culture are E. coli and K. pneumoniae [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, renal abscess may result from hematogenous spread or ascending infections due to reflux or stasis of infected urine, and the most common pathogens isolated in children are E. coli and S. aureus [3, 4, 16]. In adults, the most frequent microorganisms yielded on culture are E. coli and K. pneumoniae [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that only about 50% of children with a renal abscess have a positive urinalysis or urine culture. [16][17][18] Also common in the study population was the repeat urine dipstick. Among those with repeat urine dipsticks (performed at least 24 hours after initiation of therapy), the majority (59%) were still positive for leukocyte esterase.…”
Section: Commentmentioning
confidence: 99%
“… 3 Although rarely reported, Peptoniphilus species have been cultured from other clinical specimens, such as bone and joint specimens, pressure ulcer samples, vaginal discharges, blood, urine, spinal fluid, amniotic fluid, eye discharge, pericardial fluid, and various specimens of abscesses. 1–3 , 6–9 Currently, diseases associated with this group of reported infections include skin and soft tissue infections, 2 bone and joint infections (including prosthetic joint infections), 7 arthritis and osteomyelitis, 6 bloodstream infections, 2 urinary tract infections, 8 pulmonary pneumatoceles, 10 peritonsillar abscess, 11 renal abscess, 12 bacterial vaginosis, 13 meningitis, 14 pericarditis, 9 scrotal abscess, 3 and spinal abscess. 3 Patients infected with the organisms are often elderly, immunocompromised, and post-surgical (particularly orthopedic surgery).…”
Section: Discussionmentioning
confidence: 99%
“… 15 However, no details of these cases were mentioned. Only 6 cases (including our case) of monoinfection due to P. asaccharolyticus were described in detail, as summarized in Table 1 ; 3 , 6 , 12 , 16 , 17 3 cases associated with joints, 2 cases related to renal abscess, and 1 case of urinary tract infection. Our case is unique in that the patient was in such a severe condition that septic shock developed.…”
Section: Discussionmentioning
confidence: 99%